2018
DOI: 10.1016/j.ajpath.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Matrin 3 Is a Component of Neuronal Cytoplasmic Inclusions of Motor Neurons in Sporadic Amyotrophic Lateral Sclerosis

Abstract: Mutations in the MATR3 gene have been identified as a cause of familial amyotrophic lateral sclerosis, but involvement of the matrin 3 (MATR3) protein in sporadic amyotrophic lateral sclerosis (SALS) pathology has not been fully assessed. We immunohistochemically analyzed MATR3 pathology in the spinal cords of SALS and control autopsy specimens. MATR3 immunostaining of the motor neuron nuclei revealed two distinct patterns: mild and strong staining. There were no differences in the ratio of mild versus strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 30 publications
1
33
1
Order By: Relevance
“…These findings parallel a cellular model that showed that ALS/myopathy-associated MATR3 mutations do not produce profound changes in the localization of MATR3 (Gallego-Iradi et al, 2015 ). However, recently evidence has demonstrated that MATR3 is a component of neuronal cytoplasmic inclusions in motor neurons in cases of sporadic ALS (Tada et al, 2017 ). Surprisingly, unlike the other hnRNPs discussed in this review, stressed cells overexpressing wild-type or mutant MATR3 do not recruit MATR3 to stress granules or change the nuclear localization of MATR3, and do not induce the formation of inclusion-like structures in either the cytoplasm or nucleus (Gallego-Iradi et al, 2015 ).…”
Section: Matr3mentioning
confidence: 99%
“…These findings parallel a cellular model that showed that ALS/myopathy-associated MATR3 mutations do not produce profound changes in the localization of MATR3 (Gallego-Iradi et al, 2015 ). However, recently evidence has demonstrated that MATR3 is a component of neuronal cytoplasmic inclusions in motor neurons in cases of sporadic ALS (Tada et al, 2017 ). Surprisingly, unlike the other hnRNPs discussed in this review, stressed cells overexpressing wild-type or mutant MATR3 do not recruit MATR3 to stress granules or change the nuclear localization of MATR3, and do not induce the formation of inclusion-like structures in either the cytoplasm or nucleus (Gallego-Iradi et al, 2015 ).…”
Section: Matr3mentioning
confidence: 99%
“…TDP43 also plays a role in RNA stability and homeostasis [158], and whole genome RNA instability has been recently demonstrated in fibroblasts from individuals with ALS [159]. TDP43 interacts with other RNA processing factors, such as Matrin-3 (MATR3) and Fused-insarcoma (FUS) [160,161], that are frequently mutated in ALS [161][162][163][164]. While MATR3 is involved in polyadenylation site selection and intron retention via interactions with PABPN1 [162][163][164], FUS is a RBP that colocalizes with wild-type TDP43 in cytoplasmic inclusion bodies in models of ALS [161].…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…A total of 13 pathogenic MATR3 mutations have now been identified, most of which result in amino acid substitutions within disordered stretches of the MATR3 protein ( Figure 1A ) ( Millecamps et al, 2014 ; Lin et al, 2015a ; Origone et al, 2015 ; Leblond et al, 2016 ; Xu et al, 2016 ; Marangi et al, 2017 ). Additionally, post-mortem analyses demonstrated MATR3 pathology—consisting of cytoplasmic MATR3 accumulation as well as strong nuclear immunostaining—in patients with sporadic ALS and familial disease due to C9orf72 hexanucleotide expansions and FUS mutations ( Dreser et al, 2017 ; Tada et al, 2018 ). Together, these observations suggest that MATR3 may be a common mediator of disease even in those without MATR3 mutations.…”
Section: Introductionmentioning
confidence: 99%